2017
DOI: 10.1159/000454729
|View full text |Cite
|
Sign up to set email alerts
|

Lung Function in Women with Idiopathic Central Precocious Puberty: A Pilot Study

Abstract: Background: Studies have reported that women with early menarche (≤10 years) have lower lung function. Aim: To investigate lung function in women with a history of idio pathic central precocious puberty (ICPP) treated during childhood with gonadotropin-releasing hormone agonist (GnRHa). Methods: ICPP women (n = 23) were compared with healthy age-matched controls (n = 23). Subjects were clinically evaluated by means of a questionnaire, baseline and post-β2 agonist spirometry, impulse oscillometry (a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Two previous studies reported reduced FEV 1 in adult women who experienced menarche before age 1010 12 but neither found evidence of an association between age at menarche and FEV 1 /FVC. A Mendelian randomisation study of adolescent and adult women across multiple European cohorts, including a subset from UK Biobank, estimated a 24.8 mL increase in FVC per year increase in age at menarche among adult women and a −56.6 mL decrease in FVC per year increase in age at menarche among adolescent girls 11.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Two previous studies reported reduced FEV 1 in adult women who experienced menarche before age 1010 12 but neither found evidence of an association between age at menarche and FEV 1 /FVC. A Mendelian randomisation study of adolescent and adult women across multiple European cohorts, including a subset from UK Biobank, estimated a 24.8 mL increase in FVC per year increase in age at menarche among adult women and a −56.6 mL decrease in FVC per year increase in age at menarche among adolescent girls 11.…”
Section: Discussionmentioning
confidence: 76%
“…There is more evidence regarding the relationship between female reproductive health indicators and lung function. Early menarche,10–12 nulliparity,13 younger age at first pregnancy12 and postmenopausal status14–19 have each been associated with reduced lung function. Evidence of the effects of HRT is contradictory 14 15 20 21.…”
Section: Introductionmentioning
confidence: 99%
“…It is also a critical period for the maturation of lung function [11]. It has been previously shown that age at menarche (in females), body hair growth (in males), and peak height velocity (in both sexes) are associated with lung function in later life [11][12][13][14][15]. For instance, early menarche is associated with better lung function development in adolescence, but the opposite in adulthood [13].…”
Section: Introductionmentioning
confidence: 99%
“…20 On the other hand, there is a correlation between exposure to oestrogen and pathologic proliferative alteration in airway smooth muscle cells; and women with idiopathic central precocious puberty seem to have lower lung function despite treatment with gonadotropin releasing hormone agonist (GnRHa). 21 The main aim of this study was to investigate menarcheal age and menarcheal determinants in adolescents affected by chronic respiratory diseases such as CF and asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with mild chronic asthma experienced menarche earlier (9.2 years) than those with sporadic asthma (11.43 years) 20 . On the other hand, there is a correlation between exposure to oestrogen and pathologic proliferative alteration in airway smooth muscle cells; and women with idiopathic central precocious puberty seem to have lower lung function despite treatment with gonadotropin releasing hormone agonist (GnRHa) 21 …”
Section: Introductionmentioning
confidence: 99%